Is self-esteem predictor of in-group bias and out-group discrimination? - Jelić, Margareta (2009)
Previous research has found that, in cases of intergroup conflict, people are likely to evaluate their groups more positively than the groups they do not belong to, but are also more ready to derogate the out-group. Two important factors need to be taken into consideration to explain these processes: self-esteem and group status. We explored the role of personal and social self-esteem in predicting in-group bias and out-group discrimination on two conflicted ethnic groups living in Vukovar. Consistent with the Social Identity Theory and Social Dominance Theory our re- sults confirm that group status has impact on the self-esteem level in the way that members of the majority group tend to have higher social self-esteem. Furthermore, individuals with higher social self-esteem are more ready to express show more in-group bias and more out-group discrimination than individuals with low social self-esteem. Personal self-esteem proved to be less important in intergroup context. However, opposite to results of Long and Spears (1997), we suggest that it is individuals with high social and low personal self-esteem who express most in-group bias and out-group discrimination in order to enhance or maintain high social self-esteem and compensate for the lack of self-worth. The importance of environmental and political context for investigating group processes is discussed.
Projekt MZOS
ENG